2011
DOI: 10.1111/j.1365-3164.2011.00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Papillomaviral DNA and increased p16CDKN2A protein are frequently present within feline cutaneous squamous cell carcinomas in ultraviolet‐protected skin

Abstract: Squamous cell carcinomas (SCCs) are common feline skin tumours. While exposure to ultraviolet (UV) light causes some SCCs, a subset develop in UV-protected skin. In cats, papillomaviruses (PVs) cause viral plaques and Bowenoid in situ carcinomas (BISCs). As both may progress to SCC, it was hypothesized that SCCs in UV-protected skin may represent neoplastic transformation of a PV-induced lesion. To investigate this hypothesis, PCR was used to amplify PV DNA from 25 UV-protected and 45 UV-exposed SCCs. Oncogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 28 publications
(57 reference statements)
6
75
0
Order By: Relevance
“…However, as PVs can asymptomatically infect feline skin, 28 the detection of PV DNA within a cutaneous SCC does not prove that the virus influenced neoplasm development. As has been reported, 22 PV DNA was detected in the present study more frequently in SCCs from UV-protected areas than in SCCs from UV-exposed skin. In people, protection from UV light decreases asymptomatic PV skin infection.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…However, as PVs can asymptomatically infect feline skin, 28 the detection of PV DNA within a cutaneous SCC does not prove that the virus influenced neoplasm development. As has been reported, 22 PV DNA was detected in the present study more frequently in SCCs from UV-protected areas than in SCCs from UV-exposed skin. In people, protection from UV light decreases asymptomatic PV skin infection.…”
Section: Discussionsupporting
confidence: 88%
“…20 Associations between increased p16 and the presence of PV DNA within feline cutaneous SCCs have been reported. 21,22 However, this is the first evidence to suggest that feline PV infection could increase p16 by degrading pRb. While these results suggest that feline PV infection may alter cellular regulation by disrupting the pRb/p16 pathway, it cannot be confirmed that this action influences neoplastic transformation of the cells.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Early evidence of this was the observation of transitional lesions between papillomavirus-induced premalignant lesions and SCCs (Baer & Helton, 1993). Subsequently FcaPV-2 DNA was detected in *50 % of all feline cutaneous SCCs, in particular 76 % of those that occur in densely haired skin (Munday et al, 2011b). In comparison, FcaPV-2 DNA was found in v10 % of non-SCC skin lesions (Munday et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%